Simulation approach to process analysis of aerospace remanufacturing operations - Ng, Vannessa Kit May (2016)
Remanufacturing is performed on a variety of products, particularly those with high replacement costs such as aircraft engine components. The drivers of remanufacturing include several environmental, economic and societal benefits. Nevertheless, the remanufacturing industry faces a number of issues such as uncertainties in quantity, quality and timing of core returns which often results in stochastic routings of the product. This gives rise to the challenge of process flow analysis and makes the determination of necessary resources including station and manpower requirements difficult. As such, this report will analyse and investigate the remanufacturing processes for two aircraft engine components; the high pressure compressor blade (HPCB) and nozzle guide vane (NGV) through the use of a discrete event simulation software, Tecnomatix® Plant Simulation. After development, verification and validation of the simulation models, they are used to analyse the current process flow of two case studies. Subsequently, problems in the current process are identified and alternatives proposed to improve the process flow. Case study one and two looked into the analysis of the HPCB and NGV process flow respectively. The measure of performance used in the analysis of both plants include the remanufacturing turn-around-time (RTAT), average service time for each station, waiting time and queue length. Analysis of the current process flow highlighted inadequate machines and stations in certain work areas. With that, alternative process flows which looked into the placement of additional machines and stations were proposed and investigated further. The alternative process flows were evaluated on its suitability for implementation. For the HPCB remanufacturing plant, the incorporation of one additional pre-inspection station resulted in reduction in RTAT by 66%. On the other hand, the NGV remanufacturing plant showed a reduction in RTAT by about 12% with an additional In-process inspection station. Further reduction of about 2.5% could be achieved with the addition of a laser drill machine and an EDM. However, from an economical point of view, such minimal reduction may not justify the purchase of two additional machines.